Analyzing the impact of education policy on the quality of education in disadvantaged areas in Bongan sub-district, Kutai Barat district - Karmilasari, Vina; Utami, Anisa; Puspawati, Ani Agus (Journal of Research in Social Science and Humanities, 2023)
This research aims to analyze the impact of education policy on the quality of education in disadvantaged areas, particularly in the Bongan sub-district, Kutai Barat district. Using qualitative research methods, this study collected data through in-depth interviews and observations of education policy implementation in the field. The research found that despite policies designed to improve access and quality of education, challenges such as lack of infrastructure, inadequate human resources, and low community participation still hinder the achievement of the expected quality of education. The research indicators used include 1) education accessibility and infrastructure, 2) Learning outcomes 3) Community participation, and 4) Community welfare in the education process. The research results are expected to provide recommendations for policymakers to formulate more effective strategies for improving the quality of education in disadvantaged areas.